2022
DOI: 10.3390/antiox11122436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glyphosate on the Development of Insulin Resistance in Experimental Diabetic Rats: Role of NFκB Signalling Pathways

Abstract: Glyphosate, an endocrine disruptor, has an adverse impact on human health through food and also has the potential to produce reactive oxygen species (ROS), which can lead to metabolic diseases. Glyphosate consumption from food has been shown to have a substantial part in insulin resistance, making it a severe concern to those with type 2 diabetes (T2DM). However, minimal evidence exists on how glyphosate impacts insulin-mediated glucose oxidation in the liver. Hence the current study was performed to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
0
13
0
1
Order By: Relevance
“…In a study of male rats, Prasad et al. 33 found a dose-related increase in fasting blood glucose and serum insulin in glyphosate-exposed groups in comparison with controls. To our knowledge, the association of glyphosate with insulin resistance and other metabolic disorders has not been previously explored in human populations, although researchers have hypothesized that glyphosate has the potential to induce metabolic disease because of its ability to induce oxidative stress in preadipocytes and in other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of male rats, Prasad et al. 33 found a dose-related increase in fasting blood glucose and serum insulin in glyphosate-exposed groups in comparison with controls. To our knowledge, the association of glyphosate with insulin resistance and other metabolic disorders has not been previously explored in human populations, although researchers have hypothesized that glyphosate has the potential to induce metabolic disease because of its ability to induce oxidative stress in preadipocytes and in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…20 Animal 24 28 and human 29 31 studies have suggested that exposure to glyphosate may be related to liver disease, and some researchers have hypothesized a potential relationship with metabolic disorders. 32 , 33 In the current study, we investigated the association of prenatal and childhood exposure to glyphosate and AMPA—as indicated by urinary concentrations and registry data of nearby agricultural use of glyphosate—with markers of liver inflammation and metabolic syndrome in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers have shown that oxidative stress, inflammatory response, and lipid metabolism disorder were the most common pathogenic features of GLY-induced liver injury. The overproduction of ROS could alter the levels and activities of antioxidants including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [75][76][77]. Oxidative stress can activate inflammatory reaction pathways leading to the production of proinflammatory factors (IL-1β, IL-6, IL-10, IFN-γ, TNF-α) [47,76,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of ROS could alter the levels and activities of antioxidants including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [75][76][77]. Oxidative stress can activate inflammatory reaction pathways leading to the production of proinflammatory factors (IL-1β, IL-6, IL-10, IFN-γ, TNF-α) [47,76,78,79]. In addition, ROS and oxidative stress may result in lipid peroxidation or even oxidative damage of lipids [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…NFKBIB and NFKB are connected in the cytoplasm. Increased NFKBIB/NFKB signaling activity may be a significant factor in T2DM inflammation and insulin resistance ( 170 ). Fatty acyl-CoAs are an example of an inflammatory factor that activates NFKBIB kinase, phosphorylates NFKBIB and then translocates to the nucleus to bind to target genes, thus increasing the production of inflammatory cytokines that are involved in atherosclerosis (TNF, IL1B, IL6 and PKC) ( 171 , 172 ).…”
Section: Mechanism Of Ceramides In Atherosclerosismentioning
confidence: 99%